Impact and semi-static performance of reinforced thermoplastic composites - Akash S/O Singaram (Nanyang Technological University, 2024)
Composites, renowned for their high specific strength and stiffness, find extensive use in aerospace applications, with Thermoset (TS) Composites commonly preferred. However, the resurgence of interest in Thermoplastic (TP) Composites, owing to improved impact resistance and recyclability, has led to the exploration of fillers to enhance their performance. Notably, studies on CF/PA6 TP composites with core-shell rubber (CSR) fillers remain limited. This report investigated the behaviour and damage experiences of TP woven composites, with CSR fillers (pristine, 2 wt%, and 4 wt%) dispersed at the ply interfaces, under impact (load, displacement and energy characteristics), bending, and compressive loads, contributing insights for future TP composite structures. The report focused on fabricating TP composite samples, conducting semi-static impact tests, and analyzing load and failure mechanisms quantitatively. Semi-static tests, following ASTM standards, reveal the optimal configuration at 4 wt% CSR filler, demonstrating superior flexural, compression, and interlaminar shear strength along with minimal damage during fracture. Contrarily, low-velocity impact tests at varying energy levels exhibit lower stiffness at lower energies (20, 30, 40J) due to thermoplastic ductility, with the 2 wt% configuration outperforming in load-bearing, stiffness, elastic deformation recovery, and energy absorption at higher energies (50, 60, 70J). The difference in optimal configurations between semi-static and impact performance stems from varying failure mechanisms. Semi-static failures, mainly delamination, are less affected by stress concentrations introduced by the 4 wt% configuration, favoring its use. Conversely, impact-based failures, primarily induced by indentation, benefit from lower stress concentration, making the 2 wt% configuration more optimal. The findings emphasise the importance of tailoring CSR filler content for specific applications and evaluating the TP composite's suitability and cost-effectiveness, particularly in aerospace. Further studies should optimise CSR filler content, considering the unique requirements of semi-static and impact scenarios. This research contributes valuable insights for designing and maintaining future TP composite structures.